STREI: a new index of right heart function in isolated severe tricuspid regurgitation by Speckle tracking Echocardiography. (3rd October 2022) - Hinojar Baydes, R; Fernandez-Golfin, C; Gonzalez-Gomez, A; Garcia-Martin, A; Monteagudo, J M; Garcia-Lunar, I; Rivas, S; Sanroman, M A; Pardo, A; Sanchez-Recalde, A; Zamorano, J L
Abstract: Background: Right ventricular (RV) performance is key in the management of patients with severe tricuspid regurgitation (TR); detection of RV dysfunction is crucial to identify on time patients that benefit from valve intervention. Conventional parameters of RV function by 2D echocardiography are influenced by changes on preload conditions and can remain unaffected until late stages of the disease. The right atrium (RA) has an important role in modulating RV filling and RA performance is impaired in severe TR. Potentially, an index that combines RV and RA function may reflect a broader view of the effects of severe TR in right heart function. Purpose: 1) to evaluate the clinical utility of combining RV and RA strain for prediction of CV outcomes and 2) to design a novel index by Speckle-tracking echocardiography (STREI index) that integrates RA and RV information Methods: Consecutive patients with at least severe TR (severe, massive or torrential TR) evaluated in the Heart Valve Clinic following a comprehensive clinical protocol were included. Consecutive control subjects and patients with permanent atrial fibrillation (AF) were included for comparison. Reservoir RA strain (RASr) and RV-free wall longitudinal strain (RV-FWLS) analysis were performed using novel, automated 2D strain analytical software (AutoStrain, Philips Medical Systems the EPIQ system, Figure 1). Novel STREI index was calculated with the formula: [2 × RV-FWLS] + RASr in absolute numbers. A combined endpoint of hospital admission due to heart failure (HF) or all-cause mortality was defined. The interobserver variability of RA strain was assessed in 30 randomly selected subjects (20 TR+5 AF+5 controls). Results: A total of 176 patients with severe TR, 20 AF patients and 20 controls subjects were included in this study. Patients with TR showed lower STREI values compared to controls and to AF patients (TR vs. controls vs. AF: 55±18 vs. 116±12 vs. 70±13, p<0, 001). After a median follow-up of 28 months (IQR: 15–48 months), n=65 patients with severe TR (37%) reached the combined endpoint. Patients with both abnormal strains (abnormal RV-FWLS and abnormal RASr strain) showed a significantly higher rate of events (Figure 2A). In a multivariable analysis, STREI index was an independent predictor of HF and mortality adjusted by vena contracta, RV end-diastolic area, NYHA class and BNP values (LR χ 2 : 46, 1, p<0, 001). A cut off value of STREI index <50% held the best accuracy to predict outcomes. An abnormal STREI index was associated with 6, 1-fold increased risk of HF or death (HR 6, 9 (3, 9–12, 3), p<0, 001, Figure 2B) Inter-observer agreements for STREI values were high (intraclass correlation coefficient = 0, 96). Conclusion: STREI index is a feasible and reproducible new parameter of RV performance that independently predicts outcomes in patients with severe TR. Randomized studies should confirm its potential to identify those patients that benefit from earlier valve interventions. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Instituto Carlos III